A taxonomic review of Rhicnogryllus (Orthoptera, Trigonidiidae, Trigonidiinae) from the Philippines - Tan, Ming Kai; Daguplo, Jiandy; Modina, Ris Menoel R.; Alo, Joanna Rose A.; Haibil, Helen H.; Mapi-Ot, Emmarie F.; Macas, Jessie Jay P.; Omandam, Junel E.; Nuñeza, Olga Macas; Yap, Sheryl A.; Robillard, Tony (Zootaxa, 2026)
The taxonomy of the crickets of the genus Rhicnogryllus Chopard, 1925 is reviewed, with a focus on species from the Philippines. Previously, only two species were known from the Philippines: the type species Rhicnogryllus fascipes Chopard, 1925 and Rhicnogryllus? paetensis Tan, Yap & Baroga-Barbecho, 2020. Based on new material collected from Mindanao and Visayas regions, we describe three new species from Mindanao: Rhicnogryllus olivaceus Tan & Alo, sp. nov., Rhicnogryllus pictus Tan & Daguplo, sp. nov. and Rhicnogryllus vittatus Tan & Daguplo, sp. nov. We also record a new locality for Rhicnogryllus bipunctatus Ingrisch, 1987 in Negros Island, having previously been known only from Borneo. Consequently, six species presently exist in the Philippines.